Rapid preparation of affinity-purified lipopolysaccharide samples for electrophoretic analysis - Valverde, Claudio (1997)
Lipopolysaccharides (LPS) are the major components of the outer membrane of gram-negative bacteria. These surface molecules are relevant both for the outer membrane stability and for the interaction of the bacteria with other organisms and with the environment (18). Extensive literature is available concerning LPS physiology in different symbiotic (parasitic) and pathogenic host-bacterial interaction systems (5,20). Physiological, biochemical and chemical approaches to study LPS functions commonly require LPS extraction and purification. In the literature, LPS have been prepared by a number of different cell disruption procedures. Protocols for LPS isolation include organic solvent extractions followed by exhaustive dialysis or evaporation steps, and their modifications (11,22).